STRATEGIES AND RECOMMENDATIONS FOR MEDICAL EDUCATION IN THE EMERGENCY DEPARTMENT: IT IS GOOD TO REMEMBER - Özlem Mıdık (Journal of Medical Education and Family Medicine)
This article is a review study based on the literature covering strategies and recommendations for medical education in the emergency department, as well as blending the knowledge and experiences of a medical educator. The aim is to draw attention to the role of medical educators as role models and to remind the professionalisation processes.